Cross-species infestation and risk of Polyphagozerra coffeae (Nietner, 1861) in sandalwood agroforestry - Shanbhag, Rashmi; Gowda, Kavya; Sundararaj, Ramachandran (Indian Journal of Agroforestry, 2026)
Globally, the economic potential of Indian sandalwood (Santalum album L.) has attracted increasing interest from countries, government agencies, and industries, leading to significant investments in its cultivation and trade. In India, species has undergone a transition from a strictly protected forestry resource to an agroforestry crop. However, multidimensional challenges such as limited availability of quality planting material, inadequate awareness about cultivation practices, trade regulations and new pest and diseases emergences hampering the wide scale adaptation of this species. Polyphagozerra coffeae, once minor pet turned into major pest over the last decade has started causing severe damage in large-scale plantations, often going undetected during early stages due to lack of awareness about its biology and symptoms of infestation. This review presents a comprehensive overview of P. coffeae with emphasis on its pest status shift, biology, damage symptoms, host range, and distribution, particularly in the context of sandalwood plantations. The pest's occurrence in countries currently expanding S. album cultivation raises concerns over its cross-border threat potential. Due to medicinal applications of sandalwood chemical pesticide, usage to control the insect is forbidden making Integrated Pest Management (IPM) is only possible approach. Key strategies for this is early pest identification and detection, host plant monitoring, plantation hygiene, intercrop planning, Visual diagnostic features and field-level indicators are also provided to aid growers in timely and accurate identification. The insights presented aim to support sustainable sandalwood cultivation and mitigate the growing risks posed by P. coffeae in diversified agroforestry systems.